The Drosophila dual-specificity ERK phosphatase DMKP3 cooperates with the ERK tyrosine phosphatase PTP-ER. - Rintelen, F.; Hafen, E.; Nairz, K. (Development, 2003)
ERK MAP kinase plays a key role in relaying extracellular signals to transcriptional regulation. As different activity levels or the different duration of ERK activity can elicit distinct responses in one and the same cell, ERK has to be under strict positive and negative control. Although numerous genes acting positively in the ERK signaling pathway have been recovered in genetic screens, mutations in genes encoding negative ERK regulators appear underrepresented. We therefore sought to genetically characterize the dual-specificity phosphatase DMKP3. First, we established a novel assay to elucidate the substrate preferences of eukaryotic phosphatases in vivo and thereby confirmed the specificity of DMKP3 as an ERK phosphatase. The Dmkp3 overexpression phenotype characterized in this assay permitted us to isolate Dmkp3 null mutations. By genetic analysis we show that DMKP3 and the tyrosine phosphatase PTP-ER perform partially redundant functions on the same substrate, ERK. DMKP3 functions autonomously in a subset of photoreceptor progenitor cells in eye imaginal discs. In addition, DMKP3 function appears to be required in surrounding non-neuronal cells for ommatidial patterning and photoreceptor differentiation.